Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) pada Pembelajaran Pendidikan Pancasila Siswa - Afriyensi, Riska; Frima, Aren; Maharani, Tidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research was conducted to determine the completeness of Pancasila education learning outcomes for 4th-grade students at SD Negeri 13 Lubuklinggau after implementing the Contextual Teaching and Learning (CTL) model. The method used in this research is experimental with a pre-experimental design, specifically one-group pretest and posttest. The population and sample in this study were all 21 students of 4th grade at SD Negeri 13 Lubuklinggau. The data collection technique used was a written test in the form of multiple-choice questions. The data analysis technique used was the Z-test. Based on the calculation results, Zcount = 1.91 and Ztable = 1.64 with α = 5% (0.05). Since Zcount ≥ Ztable (1.91 ≥ 1.64), Ho was rejected, and Ha was accepted, indicating that the Contextual Teaching and Learning (CTL) model in Pancasila education for 4th-grade students at SD Negeri 13 Lubuklinggau was significantly effective. Keywords : Contextual Teaching and Learning, Learning Outcomes, Pancasila Education.